(untitled) (Critical Journal of Social Sciences, 2026)
North Macedonia is a country with a multilingual and multhietnic society,where the use of different language has a profound impact on the social ,political and cultural life of the country.This paper examines the use of languages in North Macedonia,with a particular focus on relations between ethnic groups and the impact of language on the identity,integration and social inclusion of different groups.The paper uses a sociolingusitic approach to analyze language relations and how they affect everyday life.